2016
DOI: 10.1111/febs.13694
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional signature induced by a metastasis‐promoting c‐Src mutant in a human breast cell line

Abstract: Deletions at the C-terminus of the proto-oncogene protein c-Src kinase are found in the viral oncogene protein v-Src as well as in some advanced human colon cancers. They are associated with increased kinase activity and cellular invasiveness. Here, we analyzed the mRNA expression signature of a constitutively active C-terminal mutant of c-Src, c-Src(mt), in comparison with its wild-type protein, c-Src(wt), in the human non-transformed breast epithelial cell line MCF-10A. We demonstrated previously that the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 98 publications
(185 reference statements)
0
5
0
Order By: Relevance
“…Src was the first proto-oncogene discovered and its role in cancer progression and metastasis is well established. Activation of Src can promote transformation, invasion, tumor growth, and metastasis [ 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 ], and several studies have found that Src inhibition can reduce metastasis formation in vivo [ 228 , 232 , 234 , 235 , 236 , 238 ]. Src levels or activity are increased in many human cancers [ 219 , 230 , 237 , 241 , 242 , 243 ], and Src is essential for outgrowth of disseminated tumor cells in the bone marrow [ 240 ].…”
Section: Therapeutic Potential Of Targeting Yap/taz-tead In Cancermentioning
confidence: 99%
“…Src was the first proto-oncogene discovered and its role in cancer progression and metastasis is well established. Activation of Src can promote transformation, invasion, tumor growth, and metastasis [ 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 ], and several studies have found that Src inhibition can reduce metastasis formation in vivo [ 228 , 232 , 234 , 235 , 236 , 238 ]. Src levels or activity are increased in many human cancers [ 219 , 230 , 237 , 241 , 242 , 243 ], and Src is essential for outgrowth of disseminated tumor cells in the bone marrow [ 240 ].…”
Section: Therapeutic Potential Of Targeting Yap/taz-tead In Cancermentioning
confidence: 99%
“…Of the gene products that are downregulated in this list, OPRK1 likely controls neuroendocrine differentiation [74], NOV suppresses androgen-independent PC growth [71], CAMK2N1 suppresses growth factor-induced PI3K and MEK/ERK proliferative signaling in PC cell lines [64], STAC likely modulates proliferative signaling through its SH3 and cysteine-rich domains, butyrylcholinesterase (BCHE) likely suppresses cholinergic stimulation of PC proliferation [68], and loss-of-function mutations in sucrase-isomaltase (SI) have been associated with cancer-promoting metabolic reprogramming [103]. Importantly, in LNCaP cells, Src mainly affects gene expression specific to prostate epithelial cell pathways since there are few in common with those regulated by activated Src in MCF-10A breast epithelial cells [104]. …”
Section: Discussionmentioning
confidence: 99%
“…6B). Collagen chain components including COL28A1 are up-regulated in a transcriptional signature induced by a metastasis-promoting c-Src mutant in human breast cells 30 . In addition, COL1A1 promotes cell migration in vitro and metastasis in colorectal cancer by regulating the WNT/PCP pathway 31 .…”
Section: Combined Genetic Silencing Of Protein Translation Elongation (Eef2k) and Protein Translation Initiation (Eif4ebp1) Inhibitors Comentioning
confidence: 99%